Euglena gracilis growth and cell composition under different temperature, light and trophic conditions - Wang, Yanming; Seppänen-Laakso, Tuulikki; Rischer, Heiko; Wiebe, Marilyn G. (PloS one, 2018)
Euglena gracilis, a photosynthetic protist, produces protein, unsaturated fatty acids, wax esters, and a unique β-1,3-glucan called paramylon, along with other valuable compounds. The cell composition of E. gracilis was investigated in this study to understand how light and organic carbon (photo-, mixo- and heterotrophic conditions) affected growth and cell composition (especially lipids). Comparisons were primarily carried out in cultures grown at 23 °C, but the effect of growth at higher temperatures (27 or 30 °C) was also considered. Specific growth rates were slightly lower when E. gracilis was grown on glucose in either heterotrophic or mixotrophic conditions than when grown photoautotrophically, although the duration of exponential growth was longer. Temperature determined the rate of exponential growth in all cultures, but not the linear growth rate during light-limited growth in phototrophic conditions. Temperature had less effect on cell composition. Although E. gracilis was not expected to store large amounts of paramylon when grown phototrophically, we observed that phototrophic cells could contain up to 50% paramylon. These cells contained up to 33% protein and less than 20% lipophilic compounds, as expected. The biomass contained about 8% fatty acids (measured as fatty acid methyl esters), most of which were unsaturated. The fatty acid content of cells grown in mixotrophic conditions was similar to that observed in phototrophic cells, but was lower in cells grown heterotrophically. Heterotrophic cells contained less unsaturated fatty acids than phototrophic or mixotrophic cells. α-Linolenic acid was present at 5 to 18 mg g-1 dry biomass in cells grown in the presence of light, but at < 0.5 mg g-1 biomass in cells grown in the dark. Eicosapentaenoic and docosahexaenoic acids were detected at 1 to 5 mg g-1 biomass. Light was also important for the production of vitamin E and phytol.